EFEKTIVITAS MODEL THINK PAIR SHARE DALAM PEMBELAJARAN TEMATIK INTEGRATIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH - Ika Diah Kurniawati, Husni Wakhyudin, (MALIH PEDDAS, 2014)
âThe Effectiveness of Think Pair Share Model in Learning Integrative Thematic of Problem Solving Ability at the Fourth Grade of Waru Demak State Elementary Schoolâ. The objective of the study is to know the effectiveness of think pair share model in learning integrative thematic of problem solving ability at the fourth grade of Waru Demak state elementary school. The research used quantitative method. The sample of the study is the fourth grade of A which has thirty students and the fourth grade of B which has also thirty students in Waru Demak state elementary school. It was taken by saturated sampling technique. The research design used quasi experimental design by using pretest-posttest control group design. The result of the study on the beginning analysis is to test the normality by using liliefors and the homogeneity by using F test. It is known the result is both of two classes are normal distribution and concluded that both classes are homogeny. The data got at the end of the study, it can be concluded that both classes are normal distribution and concluded that both classes are homogeny. For counting KKM test with left side test, it got concluded that problem solving ability in the experimental class reach KKM 70. It means problem solving ability in the experimental class is better than in the control class. The correlation test can be concluded that the relation between the brave character and the relationship of problem solving ability in the experimental class. It can be concluded that Think Pair Share (TPS) Model is effective to increase the ability of problem solving in learning integrative thematic at the Fourth Grade of Waru Demak State Elementary School.. Â